2020
DOI: 10.1016/j.cell.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Signaling in Muscularis Macrophages Limits Infection-Induced Neuronal Loss

Abstract: Highlights d Enteric pathogens trigger reversible neuronal loss and longterm GI symptoms d Enteric infection-triggered neuronal loss is Nlrp6and caspase 11-dependent d Intestinal muscularis macrophages (MMs) rapidly respond to enteric pathogens d Neuronal death is limited by a MM-b 2 -adrenergic-arginase 1polyamine axis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
236
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(246 citation statements)
references
References 69 publications
9
236
0
1
Order By: Relevance
“…Additional CG-SMG targets such as the spleen, pancreas, and liver may also be regulated by the microbiota with conceivable impact on systemic immunity and metabolism. Furthermore, sympathetic signalling can impact gene transcription in a variety of cell targets found in the intestine and elsewhere, including gut–resident macrophages and innate lymphoid cells 10 , 29 , 30 . We identified multiple potential microbiota–derived signals that can modulate gut sympathetic activity and neuronal populations synaptically connected to the gut.…”
mentioning
confidence: 99%
“…Additional CG-SMG targets such as the spleen, pancreas, and liver may also be regulated by the microbiota with conceivable impact on systemic immunity and metabolism. Furthermore, sympathetic signalling can impact gene transcription in a variety of cell targets found in the intestine and elsewhere, including gut–resident macrophages and innate lymphoid cells 10 , 29 , 30 . We identified multiple potential microbiota–derived signals that can modulate gut sympathetic activity and neuronal populations synaptically connected to the gut.…”
mentioning
confidence: 99%
“…135 Recent studies have demonstrated that intestinal infections can lead to a rapid loss of neurons and that macrophages can play a neuroprotective role in preventing neuronal cell death via β2-adrenergic receptor signaling. 136…”
Section: Macrophages and Developmentmentioning
confidence: 99%
“…However, there are still many questions on how enteric neurogenesis is regulated and to what extent the microbiota contributes to it. Nevertheless, the importance of this mechanism is underscored by the recent work from Matheis and colleagues, in which the authors showed that infection-induced neuronal loss can be reversed following reconstitution of the normal gut microbiota after Abx treatment [66].…”
Section: Discussion 341mentioning
confidence: 99%